2006
DOI: 10.1016/j.otohns.2005.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Soft Palate Implants for the Treatment of Mild to Moderate Obstructive Sleep Apnea

Abstract: C-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 18 publications
(32 reference statements)
0
38
2
Order By: Relevance
“…The clinical relevance of the results of this study may be that palate implants may significantly improve simple snoring and mild OSA in a small proportion of subjects with minimal morbidity and may represent an attractive first step alternative to traditional UPPP for isolated patients (19). This study suggests that proper patient selection is the most important factor to achieve high success rates from the pillar procedure.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The clinical relevance of the results of this study may be that palate implants may significantly improve simple snoring and mild OSA in a small proportion of subjects with minimal morbidity and may represent an attractive first step alternative to traditional UPPP for isolated patients (19). This study suggests that proper patient selection is the most important factor to achieve high success rates from the pillar procedure.…”
Section: Discussionmentioning
confidence: 64%
“…This study agrees with earlier studies that the pillar system reduces snoring; also, VAS decreased among bed partners, and AHI decreased at the 3-month follow-up. Most studies about OSA (16)(17)(18)(19) found no relation between VAS and AHI. In this study, we observed a slight correlation between AHI and VAS.…”
Section: Discussionmentioning
confidence: 98%
“…However, there has been a large development in treatment of these conditions over the past 20 years (3). Currently, there are several publications that evaluate the success of the pillar palatal implant system, which is frequently used to treat snoring (6)(7)(8). UPF surgery is usually recommended in patients who possess a convenient anatomic structure and a similar degree of respiratory disorder during sleep with the pillar palatal implant (in patients with a simple snoring, mild, or moderate apnea).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the Pillar Palatal Implant technique was done under local anesthesia to patients who did not show any signs of retropalatal obstruction. Operations were applied according to a classic route (6)(7)(8)(9)(10)(11)(12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation